What is a medical decision? A taxonomy based on physician statements in hospital encounters: a qualitative study. Issue 2 (11th February 2016) - Ofstad, Eirik H; Frich, Jan C; Schei, Edvin; Frankel, Richard M; Gulbrandsen, Pål
Abstract : Objective: The medical literature lacks a comprehensive taxonomy of decisions made by physicians in medical encounters. Such a taxonomy might be useful in understanding the physician-centred, patient-centred and shared decision-making in clinical settings. We aimed to identify and classify all decisions emerging in conversations between patients and physicians. Design: Qualitative study of video recorded patient–physician encounters. Participants and setting: 380 patients in consultations with 59 physicians from 17 clinical specialties and three different settings (emergency room, ward round, outpatient clinic) in a Norwegian teaching hospital. A randomised sample of 30 encounters from internal medicine was used to identify and classify decisions, a maximum variation sample of 20 encounters was used for reliability assessments, and the remaining encounters were analysed to test for applicability across specialties. Results: On the basis of physician statements in our material, we developed a taxonomy of clinical decisions—the Decision Identification and Classification Taxonomy for Use in Medicine (DICTUM). We categorised decisions into 10 mutually exclusive categories: gathering additional information, evaluating test results, defining problem, drug-related, therapeutic procedure-related, legal and insurance-related, contact-related, advice and precaution, treatment goal, and deferment. Four-coder inter-rater reliability using Krippendorff's α was 0.79. Conclusions: DICTUM represents a precise, detailed and comprehensive taxonomy of medical decisions communicated within patient–physician encounters. Compared to previous normative frameworks, the taxonomy is descriptive, substantially broader and offers new categories to the variety of clinical decisions. The taxonomy could prove helpful in studies on the quality of medical work, use of time and resources, and understanding of why, when and how patients are or are not involved in decisions.